Análise do comportamento das unidades quadrilaterais polarizadas de relé de distância frente a curtos-circuitos em linhas de transmissão - Gustavo Rafael de Souza Reis (2015)
This paper presents the study, implementation and analysis of a digital distance relay Quadrilateral Polarized with various types of polarizations. Therefore, it was found behavior for various faults at certain points on the transmission line, as follows: a little front of the relay, in busbar, behind the relay (considering a reverse fault) and far ahead of the busbar (in the Zone 1 protection). An investigation is made of resistive reach as well as the influence of factors that directly affect the functionality of the relay, in order to investigate the change in their operating characteristics for various points on the line defect. They were discriminated to signal processing steps in the implementation of the protection algorithm. In these steps, it demonstrated the importance of data processing, since it is crucial to proper functioning and validation of the digital distance relay. The simulations were implemented through the MATLAB software, and the behavior was observed in the form of R-X diagrams from data generated by the EMTP-ATP, using the graphical tool ATP-DRAW. An evaluation of the responses obtained from the tests is made, showing the dynamic displacement of the protection zone under the influence of fault conditions, polarizations voltages used and, especially, by varying the fault resistance, which affects directly the line protection transmission. Finally the conclusions and suggestions for future works are presented.